Educational leadership in the Vietnamese context - Truong , Thi My Dung (Tạp chí Khoa học Trường Đại học Sư phạm Thành phố Hồ Chí Minh, 2019)
This paper summarises some significant findings from a study conducted at a university in the South of Vietnam. The research explored how Vietnamese educational leaders understand educational leadership. The aim of the paper is to raise awareness of educational leadership in higher education among Vietnamese educational leaders, to help improve the quality of leadership work at this university, and other universities throughout the country.